Exosomes Regulate the Epithelial–Mesenchymal Transition in Cancer - Jiang, Jingwen; Li, Jiayu; Zhou, Xiumei; Zhao, Xueqin; Huang, Biao; Qin, Yuan (Frontiers in Oncology, 2022)
Exosomes are important mediators of intercellular communication and participate in complex biological processes by transferring a variety of bioactive molecules between cells. Epithelial–mesenchymal transition (EMT) is a process in which the cell phenotype changes from epithelioid to mesenchymal-like. EMT is also an important process for cancer cells by which they acquire invasive and metastatic capabilities, which aggravates the degree of tumor malignancy. Numerous studies have demonstrated that exosomes encapsulate various components, such as microRNAs and proteins, and transfer information between tumor cells or between tumor cells and the tumor microenvironment, thereby regulating the EMT process. Exosomes can also be used for cancer diagnosis and treatment or as a drug delivery platform. Thus, they can be used as a therapeutic tool to control the occurrence of EMT and affect cancer progression. In this review, we summarize the latest research advancements in the regulation of the EMT process in tumor cells by the contents of exosomes. Furthermore, we discuss the potential and challenges of using exosomes as a tool for cancer treatment.